Recycled Glass as a Substitute for Quartz Sand in Silicate Products - Borek, Katarzyna (Materials (Basel), 2020)
In 2016, an average of 5.0 tons of waste per household was generated in the European Union (including waste glass). In the same year, 45.7% of the waste glass in the EU was recycled. The incorporation of recycled waste glass in building materials, i.e., concrete, cements, or ceramics, is very popular around the world because of the environmental problems and costs connected with their disposal and recycling. A less known solution, however, is using the waste glass in composite products, including sand-lime. The aim of this work was to assess the role of recycled container waste glass in a sand-lime mix. The waste was used as a substitute for the quartz sand. To verify the suitability of recycled glass for the production of sand-lime products, the physical and mechanical properties of sand-lime specimens were examined. Four series of specimens were made: 0%, 33%, 66%, and 100% of recycled waste glass (RG) as a sand (FA) replacement. The binder mass did not change (8%). The research results showed that ternary mixtures of lime, sand, and recycled waste glass had a higher compressive strength and lower density compared to the reference specimen. The sand-lime specimen containing 100% (RG) increased the compressive strength by 287% compared to that of the control specimen. The increase in the parameters was proportional to the amount of the replacement in the mixtures.